A systematic methodology to calibrate wellbore failure models, estimate the in-situ stress tensor and evaluate wellbore cross-sectional geometry. (January 2022) - Dahrabou, Asmae; Valley, Benoît; Meier, Peter; Brunner, Philip; Alcolea, Andrés
Abstract: Deep geothermal boreholes, often drilled to the crystalline basement, suffer from borehole breakouts that compromise borehole stability and/or lead to low drilling performance. These issues increase the cost of deep geothermal projects and lead to irregular cross-sectional geometries that may entangle well completion (e.g., packer isolation for zonal stimulation, cementing, etc.). Thus, the proper knowledge of rock strength, state of stress and their interactions at the closest vicinity of the borehole is key to the success of deep geothermal drilling. Typically, the magnitudes of the vertical and minimum horizontal principal stresses, S v and S h m i n, respectively, can be estimated while S H m a x is difficult to constrain. This paper presents a systematic methodology to jointly evaluate the heterogeneous distributions of the stress tensor principal components and orientations, and the rock strength properties (e.g. cohesion, friction). Model parameters are estimated from measurements available during or shortly after drilling, i.e., breakout width, breakout extent/depth of penetration, breakout orientation and drilling induced tensile fractures. Additionally, measurements of estimated parameters or transformations of them can be considered in the calibration in a generic manner (e.g., S h m i n interpreted from XLOT). For illustration purposes, the methodology is applied to the extensive borehole data set along the crystalline section of the borehole BS-1, in Basel (Switzerland). The methodology allows us (1) to derive plausible sets of stress and strength parameters reproducing the complex distribution of breakouts along BS-1, and (2) to unveil the paradox of having no borehole breakouts at sections with high density of natural fractures.